A clinicopathological analysis of KISS1 and KISS1R expression in colorectal cancer. Issue 7 (22nd May 2015) - Kostakis, Ioannis D.; Agrogiannis, George; Vaiopoulos, Aristeidis G.; Mylona, Eleni; Patsouris, Efstratios; Kouraklis, Gregory; Koutsilieris, Michael
<x xml:space="preserve">Abstract</x> Kisspeptins, the products of the KISS1 gene have tumor suppressing and antimetastatic properties. We aimed to study KISS1 and KISS1R expression in colorectal cancer. We analyzed KISS1 and KISS1R expression using immunohistochemistry and image analysis in normal and malignant tissue samples from 111 patients with colorectal adenocarcinoma. KISS1 expression was much higher in the normal than in the malignant colonic mucosa. Regarding malignant tissues, KISS1 levels were higher in larger tumors, in stage III and IV cancers, in cancers with lymph node metastasis and in tumors located in the distal part of the large intestine. Patients with greater KISS1 levels had worse prognosis. No KISS1R expression was detected in normal or malignant tissues or in liver metastases. KISS1 expression is reduced during the malignant transformation of the colonic mucosa. However, larger and advanced colorectal cancers express more KISS1, without reaching the former normal levels, and increased KISS1 levels are associated with worse prognosis. Finally, neither the normal nor the malignant colonic epithelial cells produce KISS1R.